The Effectiveness of Garlic Extract (Allium sativum) against Decreased Serum Levels Tumor Necrosis Factor-α (TNF-α) in Chronic Hemodialysis Patients at Dr. Mohammad Hoesin General Hospital - Eeng Yoneska; Zulkhair Ali; Mgs. Irsan Saleh (HM Publisher, 2023)
Background: Chronic kidney disease (CKD) is a pathophysiological process with various etiologies resulting in a progressive decline in kidney function and generally ends in kidney failure. During hemodialysis, inflammation and activation of TNF-α and other proinflammatory cytokines occur. This inflammatory condition causes a decrease in the effectiveness of HD in reducing the mortality of patients with CKD. Garlic has the potential as an anti-inflammatory agent due to its high antioxidant content in garlic. This study aimed to determine the effectiveness of garlic extract (Allium sativum) on decreasing serum levels of tumor necrosis factor-α (TNF-α) in chronic hemodialysis patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study is an experimental study with a randomized, controlled, double-blind trial crossover design. A total of 40 research subjects participated in this study which was grouped into treatment (garlic extract) and placebo groups. TNF-α levels were measured using the ELISA method. Data analysis was carried out using SPSS univariate and bivariate. Results: The results of the study showed that the administration of garlic extract was able to reduce TNF-α levels by 12.5 pg/mL, p<0.05. In contrast, in the placebo group, there was an increase in TNF-α levels of 8.3 pg/mL, p<0.05. Conclusion: Garlic extract (Allium sativum) is effective in reducing tumor necrosis factor-α (TNF-α) serum levels in chronic hemodialysis patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.